Clinical evaluation of paroxysmal and permanent atrial fibrillation patients in cardiac inpatient unit: Cross-sectional study - Asoğlu, Ramazan; Özdemir, Mahmut; Aladağ, Nesim; Karadaş, Sevdegül; Asoğlu, Emin (Journal of Surgery and Medicine, 2019)
Aim: Atrial fibrillation (AF), a supra-ventricular arrhythmia, is characterized by a rapid and irregular heart rate, for which electrocardiography is the diagnostic tool. Hypertension is the most common cause of AF. In this study, we aimed to evaluate the paroxysmal AF and permanent AF patients’ symptoms, medical history, and clinical characteristics in the inpatient unit. Methods: 115 patients (30 patients with paroxysmal AF and 85 patients with permanent AF) were enrolled in the study. All patients’ detailed histories were taken; physical examination, routine biochemical tests, electrocardiographies, and transthoracic echocardiographies were performed. CHA2DS2-VASc (Congestive heart failure/left ventricular dysfunction, Hypertension, Age ≥75 years, Diabetes Mellitus, Stroke/transient ischemic attack/systemic embolism, Vascular Disease, Age 65-74 years, Sex Category) scores were recorded. Results: Permanent AF patients were older (70.0 (10.5) vs 61.4 (15.8); P=0.01) and had a lower ejection fraction (41.0 (11.9) vs 53.3 (11.2); P=0.01) than paroxysmal AF patients. CHA2DS2-VASc scores were similar between the two groups (3.0 (1.5) vs 2.7 (1.3); P=0.24). In hematological analysis, prothrombin time (15.3(1.3-106.4) vs 13.6(11.0-75.5); P=0.03) and international normalized ratio (1.2(0.9-16.0) vs 1.1(0.9-6.0); P=0.01) values were higher in permanent AF patients compared to those with paroxysmal AF. Rhythm regulation was performed to paroxysmal AF patients. Rate regulation was performed significantly more frequently in permanent AF patients than paroxysmal AF patients (74(87%)) vs (12(40%)); P=0.01). Conclusion: This study demonstrated that permanent AF patients had more comorbidities compared to paroxysmal AF patients. Rhythm control was the principal treatment strategy in paroxysmal AF, whereas rate control was the treatment of choice in permanent AF.